Core loss estimation of high speed machine - Muhammad Hanif Husni (2015)
High speed machine has become an integral part of today’s technology. High speed machine comes in many forms including induction machine, switched reluctance machine, permanent magnet and claw poles. An aircraft Auxiliary Power Unit is an example of an equipment that makes use of high speed machine. Regardless of its type, one of the few things it has in common is losses. The components that contribute to a machine’s loss includes stator and rotor loss, core loss and windage loss. Because core loss is proportionate to the frequency and speed of the machine, it is therefore important to properly estimate core loss in a high speed machine. This project will focus on developing a more accurate way of calculating core loss in high speed machine. Traditional methods of calculation such as classical Steinmetz Equation are not suitable for calculation of core loss at high speed. Because traditional methods involves assumptions such as a constant sinusoidal and uniformly distributed flux density, calculation would lead to large errors. In addition, relying on steel sheet manufacturers’ core loss data alone is not sufficient as it mainly meant for low speed application. It is therefore important to produce a method that would take into account the effects that high speed machine faces. This include doing polynomial fitting on existing data to obtain accurate core loss coefficients. In addition, the relationship of these coefficients to flux density was studied. Based on these methods, a more accurate manner of calculating core loss was achieved. In addition, this report will discuss on flux distribution in a machine. The non-uniform distribution of flux density is an important factor that has to be taken into effect when calculating core loss. Simulation was done to study this behaviour of an electrical machine.